Prevalence of microorganisms causing catheter associated urinary tract infections (CAUTI) among catheterised patients admitted in a tertiary care hospital - M., Vinoth; R., Prabagaravarthanan; M., Bhaskar (International Journal of Research in Medical Sciences, 2017)
Background: Catheter-associated urinary tract infection (CAUTI) is an important cause of morbidity and mortality in Indian subjects, affecting all age groups. Bacteriuria orcandiduria is almost inevitable in nearly half of the patients who require an indwelling urinary catheter for more than 5 days. The objective of this study was to find the prevalence of CAUTI infection and to determine their antibiotic profile Methods: The present cross-sectional study included 50 patients admitted to medicine and surgery wards in our hospital. The urine from catheter is collected from each patient and subjected to culture and antibiotic susceptibility testing. Results: The prevalence of catheter associated urinary tract infection in our hospital is about 20% and asymptomatic bacterial colonization is 50% which is nearequal to Danchaivijitr S et al study. The common pathogens found in this study are Escherichia coli (22%), Klebsiella (18%), Enterobacter (8%), Staph. aureus (6%) which include MRSA (4%), Pseudomonas (6%), Enterococcus (4%), Candida sps. (4%) Andproteus (2%). Conclusions: CAUTI has low prevalence 20% and asymptomatic colonisation 50% in our hospital with common pathogen being Escherichia coli. It is one of the important notable pathogen causing nosocomial infection among admitted patients. The patients present mainly as asymptomatic bacterial colonisation and risk of CAUTI increases with longer duration of catheterisation. All patients those who had catheter for more than 6 days, aged 60 and above, should be checked for UTI symptoms. And their urine should be cultured regularly in order to diagnose and prevent CAUTI and its complications which are very dangerous and difficult to treat.